An Epigenetic Alphabet of Crop Adaptation to Climate Change - Guarino, Francesco; Cicatelli, Angela; Castiglione, Stefano; Agius, Dolores R.; Orhun, Gul Ebru; Fragkostefanakis, Sotirios; Leclercq, Julie; Dobránszki, Judit; Kaiserli, Eirini; Lieberman-Lazarovich, Michal; Sõmera, Merike; Sarmiento, Cecilia; et al. (Frontiers in Genetics, 2022)
Crop adaptation to climate change is in a part attributed to epigenetic mechanisms which are related to response to abiotic and biotic stresses. Although recent studies increased our knowledge on the nature of these mechanisms, epigenetics remains under-investigated and still poorly understood in many, especially non-model, plants, Epigenetic modifications are traditionally divided into two main groups, DNA methylation and histone modifications that lead to chromatin remodeling and the regulation of genome functioning. In this review, we outline the most recent and interesting findings on crop epigenetic responses to the environmental cues that are most relevant to climate change. In addition, we discuss a speculative point of view, in which we try to decipher the “epigenetic alphabet” that underlies crop adaptation mechanisms to climate change. The understanding of these mechanisms will pave the way to new strategies to design and implement the next generation of cultivars with a broad range of tolerance/resistance to stresses as well as balanced agronomic traits, with a limited loss of (epi)genetic variability.